Sensors and instrumentation, aircraft/aerospace and energy harvesting. proceedings of the 36th IMAC, a conference and exposition on structural dynamics 2018 /: proceedings of the 36th IMAC, a conference and exposition on structural dynamics 2018. Volume 8 : (2019) - Unknown
No abstract available